Endocuticle sclerotisation increases the mechanical stability of cuticle. Issue 41 (25th September 2019) - Wang, Lu-Yi; Jafarpour, Mohsen; Lin, Chung-Ping; Appel, Esther; Gorb, Stanislav N.; Rajabi, Hamed
Abstract : Pachyrhynchus weevils are equipped with a sclerotised endocuticle, which is surprisingly stiffer than their exocuticle. Abstract : The cuticle plays an important role in the evolutionary success of insects. Many studies on insect cuticles have reported a soft, resilin-rich endocuticle. However, a recent study indicated the presence of a sclerotised endocuticle in the weevil Pachyrhynchus sarcitis kotoensis, which contradicts former knowledge. To understand the degree of sclerotisation in the endocuticle of the weevil and its potential function, we first examined the endocuticle by microscopic and staining techniques. We next performed mechanical tests to measure the material properties of the endocuticle, and numerical simulations to predict the structural effect of the sclerotisation. Our results provide the first evidence of the existence of a sclerotised endocuticle and its remarkable function in improving the mechanical stability of the cuticle. This study highlights the finding of a high degree of sclerotisation in the stiff endocuticle of the weevil, especially the matrix surrounding the fibres. This novel case brings new understanding of cuticle properties and gives promising insights into biomaterial design.